Post-traumatic stress and future substance use outcomes: leveraging antecedent factors to stratify risk - Garrison-Desany, Henri M.; Meyers, Jacquelyn L.; Linnstaedt, Sarah D.; House, Stacey L.; Beaudoin, Francesca L.; An, Xinming; Zeng, Donglin; Neylan, Thomas C.; Clifford, Gari D.; Jovanovic, Tanja; Germine, Laura T.; Bollen, Kenneth A.; et al. (Frontiers in Psychiatry, 2024)
Background. Post-traumatic stress disorder (PTSD) and substance use (tobacco, alcohol, and cannabis) are highly comorbid. Many factors affect this relationship, including sociodemographic and psychosocial characteristics, other prior traumas, and physical health. However, few prior studies have investigated this prospectively, examining new substance use, and the extent to which a wide range of factors may modify the relationship to PTSD. Methods. The Advancing Understanding of RecOvery afteR traumA (AURORA) study is a prospective cohort of adults presenting at emergency departments (N=2943). Participants self-reported PTSD symptoms, and tobacco, alcohol, and cannabis use frequency and quantity at six total timepoints. We assessed associations of PTSD and future substance use, lagged by one timepoint, using Poisson generalized estimating equations. We also stratified by incident and prevalent substance use, and generated causal forests to identify the most important effect modifiers of this relationship out of 128 potential variables. Results. At baseline, 37.3% (N=1099) of participants reported likely PTSD. PTSD was associated with tobacco frequency (incident rate ratio (IRR): 1.003, 95% CI: 1.00, 1.01; p=0.02) and quantity (IRR: 1.01, 95% CI: 1.001, 1.01; p=0.01), and alcohol frequency (IRR: 1.002, 95% CI: 1.00, 1.004; p=0.03) and quantity (IRR: 1.003, 95% CI: 1.001, 1.01; p=0.001), but not with cannabis use. There were slight differences in incident compared to prevalent tobacco frequency and quantity of use; prevalent tobacco frequency and quantity were associated with PTSD symptoms, while incident tobacco frequency and quantity were not. Using causal forests, lifetime worst use of cigarettes, overall self-rated physical health, and prior childhood trauma were major moderators of the relationship between PTSD symptoms and the three substances investigated. Conclusions. PTSD symptoms were highly associated with tobacco and alcohol use, while the association with prospective cannabis use is not clear. Findings suggest that understanding the different risk stratification that occurs can aid in tailoring interventions to populations at greatest risk, to best mitigate the comorbidity between PTSD symptoms and future substance use outcomes. We demonstrate this is particularly salient for tobacco use and, to some extent, alcohol use, while cannabis is less likely to be impacted by PTSD symptoms across strata.